2003
DOI: 10.2214/ajr.180.4.1800935
|View full text |Cite
|
Sign up to set email alerts
|

Sydney Breast Imaging Accuracy Study: Comparative Sensitivity and Specificity of Mammography and Sonography in Young Women with Symptoms

Abstract: These data show that sonography is the more accurate imaging test in women 45 years old or younger who present with breast symptoms and may be an appropriate initial imaging examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
3
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(99 citation statements)
references
References 12 publications
6
89
3
1
Order By: Relevance
“…In a study published in American journal of Roentgenology in 2003, first of its kind by N. Houssami from Sydney, Australia, show that sonography of breast is an accurate imaging test in women 45 years or younger who present with breast symptoms and may be an appropriate investigation [23]. Thus, in Indian scenario with younger age of breast cancer incidence, sonographic evaluation of young patients with breast symptoms is appropriate.…”
Section: Excised Specimenmentioning
confidence: 99%
“…In a study published in American journal of Roentgenology in 2003, first of its kind by N. Houssami from Sydney, Australia, show that sonography of breast is an accurate imaging test in women 45 years or younger who present with breast symptoms and may be an appropriate investigation [23]. Thus, in Indian scenario with younger age of breast cancer incidence, sonographic evaluation of young patients with breast symptoms is appropriate.…”
Section: Excised Specimenmentioning
confidence: 99%
“…As early-onset breast cancer in itself is associated with a poorer prognosis (Sidoni et al, 2003), it may be advantageous to initiate breast cancer screening among multiparous women with the IGF1-19/-19 genotype at an earlier age. Alternative screening methods may be needed in this age group as mammography shows poor sensitivity in young women (Houssami et al, 2003). Conversely, among patients with fewer than two children, the IGF1-19/-19 genotype was associated with a later age of breast cancer onset, and these women may initiate screening at a later age.…”
Section: Igf1-19/-mentioning
confidence: 99%
“…Many published studies have confirmed that the sensitivity of mammography increases with age. 9,10 The sensitivity of mammography may be decreased further in women who carry a deleterious mutation in BRCA1 or BRCA2; pilot studies evaluating mammography in BRCA1 and BRCA2 carriers have found a high rate of false-negative results. 6,11,12 This may be attributable both to increased breast density in young women and to tumor phenotype, including features such as pushing margins, which may contribute to a smooth appearance rather than a spiculated appearance of a mass on mammography.…”
mentioning
confidence: 99%